Morphometrics and Life Cycle Study of Cabbage Butterfly, Pieris brassicae nepalensis (Doubleday) in Ilam, Nepal - Subedi, A.; Tiwari, S. (Journal of Agriculture and Environment, 2021)
Cabbage butterfly, Pieris brassicae nepalensis is an economic pest of crucifer crops. Morphometrics and life cycle study of P. brassicae was carried out in room condition at Barhabasti, Ilam, Nepal to understand their general morphology and life cycle. Based on the results of morphometric parameters, the mean length of egg, larva (I - V instars), pre-pupa, pupa and adult was measured 1.28 mm, 3.97 mm, 8.50 mm, 20.78 mm, 33.6 mm, 38.72 mm, 39.32 mm, 26.04 mm, and 24.08, respectively. The adult wingspan of female was greater than male wingspan. The adult butterflies were pale white with dense hairs and the females contain two small (black) dots in the central area of each forewing and one (black) dot in males. Egg, larval (I to V instars), pre-pupa and pupal life durations were 4 to 5 days, 3-5 days, 4-6 days, 4-5 days, 4-5 days, 4-6 days, 1-2 days, 8-10 days, respectively. The total development period from egg to adult was 32 to 44 days. This information’s are useful for ecologist and to develop an integrated pest management protocol.